circRNA Expression Pattern and circRNA–miRNA–mRNA Network in HCs, HSCs, and KCs of Murine Liver After Echinococcus multilocularis Infection - Liu, Tingli; Wang, Liqun; Li, Hong; Li, Yanping; Chen, Guoliang; Pu, Guiting; Guo, Xiaola; Zheng, Yadong; Bai, Xue; Luo, Xuenong (Frontiers in Veterinary Science, 2022)
Caused by Echinococcus multilocularis (E. multilocularis), the alveolar echinococcosis is reported every year around the word and severely threaten the safety of human beings and animals. However, the molecular interaction relationships s between host and E. multilocularis is still remain unclear. With multiple functions, circRNA plays a crucial role in regulating the development of parasitic disease. With that in mind, the main purpose of this study was to reveal the circRNAs expression profiles and circRNA-miRNA-mRNA network relationships in hepatocytes (HCs), hepatic stellate cells (HSCs), and Kupffer cells (KCs) of murine liver after E. multilocularis infection. After sequencing, 6290 circRNAs were identified from 12 hepatic cells samples. Based on the subsequent analysis, 426 and 372 circRNAs were significantly different in HCs expression two and three months after E. multilocularis infection, and similar results also demonstrated in HSCs (426 and 372 circRNAs) and KCs (429 and 331 circRNAs), respectively. Seven candidate circRNAs were selected randomly to identify the accuracy of sequencing results by using qRT-PCR. Additionally, three circRNAs-miRNA-mRNA networks in HCs, HSCs, and KCs were constructed, and these networks are essential for researches in circRNAs associated with E. multilocularis infection.